Water Deficit and Salinity Stresses Alone or Simultaneously: How Are Exogenous Salicylic Acid-Mediated Tolerance Mechanisms Enhanced in Young Citrus Plants? - Milton Carriço Sá; Raul Antonio Araújo do Bonfim; Maiara Costa Silva; Vinícius Alves Rodrigues; Laélcio Novato Ribeiro Filho; Gustavo Kawan Almeida Costa; Camila Valentim Silva Sousa; Rosilene Gomes de Souza Pinheiro; Matheus Ferreira Almeida; Natália Deniz Brito; Marcela Ferraz e Silva; Paulo Araquém Ramos Cairo (Journal of Plant Growth Regulation, 2026)
Water deficit and salinity pose significant challenges to the cultivation and distribution of citrus plants ( Citrus sinensis ) worldwide. Although these two types of abiotic stress are harmful throughout the biological cycle, they can become critical for plant survival and establishment in the early development stages. This study aimed to investigate the effects of salicylic acid (SA) foliar application on the physiological and biochemical traits of young citrus plants subjected to water deficit and salinity conditions, either alone or simultaneously. A greenhouse experiment was conducted with seven-month-old citrus plants subjected to four growing conditions - no stress, water deficit (WD), salinity (S), and WD + S - and pre-treated with SA application at 0, 1, 2, and 4 mM. Results showed that water deficit and salinity reduced gas exchange and damaged the photosynthetic apparatus by increasing reactive oxygen species (ROS) levels. Simultaneous stresses caused more photosynthetic pigment degradation and reduced gas exchange than water deficit and salinity stresses alone. The application of 2 mM SA mitigated the adverse effects of stress by improving osmoregulation and enhancing antioxidant enzyme activity and phenolic content. Furthermore, it prevented electrolyte leakage and ROS accumulation, with the intensity of these effects varying depending on the type of stress. SA also improved gas exchange under individual stresses, while increasing water-use efficiency under combined water deficit and salinity. These findings suggest the foliar application of SA as an effective strategy to improve tolerance to water deficit and salinity, whether occurring individually or in combination, in young post-transplanted citrus plants.